The Relationship between Characteristics, Attitudes and Community Participation on CSR Program Performance - Celomita Aurelia Nur Aliyas; Annisa Wahyuni Arsyad; Erwiantono Erwiantono (Journal La Sociale, 2024)
Corporate Social Responsibility (CSR) is a company's commitment to behaving ethically and contributing to sustainable development. CSR is implemented through collaboration with company stakeholders to improve people's lives. CSR prioritizes balancing the company's financial, social and environmental aspects. This research aims to determine the relationship between attitudes, participation and community characteristics on the performance of the CSR program by PT Pertamina Patra Niaga Fuel Terminal Samarinda. This study uses a quantitative approach. The total number of respondents who will be included in this research is 90 people who are members of the community who participate in the Bank Ramli CSR program by PT Pertamina Patra Niaga Fuel Terminal Samarinda. The Spearman Rank correlation test will be used to measure the relationship between variables such as characteristics, attitudes and community participation on CSR program performance. This research found that community characteristics such as community income and level of knowledge have a significant correlation with CSR program performance, while other characteristics such as gender, age, education, number of family dependents, and employment do not have a significant influence on CSR program performance. Community attitudes in the affective aspect have a significant positive correlation with the company's responsibility towards society. Apart from that, community participation in the aspect of enjoying the program also has a very significant correlation to company profits and the company's responsibility towards the community.